Self-care and quality of life among patients with breast cancer - Mega Herawati; Fauzi Ashra; Ayu Nurdiyan (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Breast cancer is the most common cancer found in women worldwide and is the second cause of cancer-related deaths after lung cancer. Breast cancer has several treatments including chemotherapy, radiotherapy, hormonal therapy, and mastectomy. Impaired physical mobility can cause self-care deficits, self-care dramatically affects the quality of life of Breast Cancer patients, but further research is needed to what extent self-care can affect the quality of life of patients. Purpose: Knowing the relationship between self-care and the quality of life of Breast Cancer patients in the Surgery Room of Dr. Achmad Mochtar Hospital Bukittinggi. Method: Mixed methods with explanatory design. The sampling technique used was a total sampling of 50 respondents for quantitative purposes and a purposive sampling technique of 5 participants for qualitative purposes. Quantitative Self-care measurement using the Barthel Index questionnaire, quality of life measurement using the SF-36 questionnaire, and qualitative using an in-depth interview guide. Qualitative data analysis using the chi square and qualitative statistical test using keywords, subcategories, categories and themes. Results: The quantitative research results show a relationship between self-care and the quality of life of breast cancer patients by sig 0.011. In qualitative research, the lower the self-care of breast cancer patients, the worse the quality of life in breast cancer patients. Conclusion: Self-care in breast cancer patients, qualitative research, the lower the self-care of breast cancer patients, the worse the quality of care. life in breast cancer patients.